2016
DOI: 10.1128/jvi.02123-15
|View full text |Cite|
|
Sign up to set email alerts
|

Cytomegalovirus-Specific CD4 T Cells Are Cytolytic and Mediate Vaccine Protection

Abstract: CD4 T cells provide protection against cytomegalovirus (CMV) and other persistent viruses, and the ability to quantify and characterize epitope-specific responses is essential to gain a more precise understanding of their effector roles in this regard. Here, we report the first two I-A d -restricted CD4 T cell responses specific for mouse CMV (MCMV) epitopes and use a major histocompatibility complex class II (MHC-II) tetramer to characterize their phenotypes and functions. We demonstrate that MCMV-specific CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 53 publications
(66 reference statements)
5
68
0
Order By: Relevance
“…This assay convincingly shows that CD4 ϩ T cells can respond directly to CMV-infected cells probably using both the cytokine expression and cytotoxicity mechanisms observed in the polyfunctional flow cytometry experiments. The ability of CMV-specific CD4 ϩ T cells to control viral dissemination is in spite of the large array of immune evasion mechanisms encoded by the virus genome and confirms the observations made in vivo in the murine model (68) and previously in infected macrophages in in vitro models of HCMV infection (69). Further interrogation of the CMV-specific CD4 ϩ T cell response using this in vitro model will be able to determine whether the cytokines or cytotoxicity produced by CD4 ϩ T cells is more important in resolving CMV infection or reactivation in the host.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This assay convincingly shows that CD4 ϩ T cells can respond directly to CMV-infected cells probably using both the cytokine expression and cytotoxicity mechanisms observed in the polyfunctional flow cytometry experiments. The ability of CMV-specific CD4 ϩ T cells to control viral dissemination is in spite of the large array of immune evasion mechanisms encoded by the virus genome and confirms the observations made in vivo in the murine model (68) and previously in infected macrophages in in vitro models of HCMV infection (69). Further interrogation of the CMV-specific CD4 ϩ T cell response using this in vitro model will be able to determine whether the cytokines or cytotoxicity produced by CD4 ϩ T cells is more important in resolving CMV infection or reactivation in the host.…”
Section: Discussionsupporting
confidence: 65%
“…This problem has been addressed to an extent in the murine model with MCMV infection. A recent study using novel epitope class II-restricted tetramers in vivo observed direct killing of infected cells (68). With respect to HCMV infections, Sinzger et al have shown that IE1-specific CD4 ϩ T cell clones are able to produce IFN-␥ in response to stimulation by TB40/E-infected macrophages which have downregulated MHC class II expression (69).…”
Section: Discussionmentioning
confidence: 99%
“…The data presented in this study suggest that MCMV-specific CD4 T cells can kill target cells in an epitope- and organ-specific manner. Additionally, they show that vaccination with CD4 T cell epitopes leads to reduced viral replication in tissues where CD4 CTL are observed (136). …”
Section: Infections In Which Cd4 Ctl Are Protectivementioning
confidence: 99%
“…Moreover, absence of TGF-β signaling did not greatly impact antiviral cytokine secretion by D b :GP 33-41 LCMV-specific CD8 T cells upon cognate peptide stimulation (Supplemental Figure 1D). We also found that TGF-β signaling only minimally suppressed the effector markers KLRG and Ly6C on virus-specific CD8 T cells, or granzyme B on IFN-γ-producing cells, after GP [33][34][35][36][37][38][39][40][41] peptide stimulation (Supplemental Figure 1, E-G). Overall, these data show that deletion of Tgfbr2 prior to infection only minimally affected CD8 T cell antiviral responses early after chronic LCMV infection.…”
Section: Cellmentioning
confidence: 99%
“…Cytokine measurements. Secretion of IFN-γ, TNF-α, and IL-2 from LCMV-specific T cells was performed ex vivo using GP [31][32][33][34][35][36][37][38][39][40][41] or GP [67][68][69][70][71][72][73][74][75][76][77] peptide stimulation of splenocytes incubated in the presence of 1 μg/ ml brefeldin A (BFA; Sigma-Aldrich) for 5 hours at 37˚C before staining.…”
Section: Cd49dmentioning
confidence: 99%